2016
DOI: 10.1177/0145721716654006
|View full text |Cite
|
Sign up to set email alerts
|

Clinical, Psychosocial, and Demographic Factors Are Associated With Overweight and Obesity in Early Adolescent Girls With Type 1 Diabetes

Abstract: Purpose-The purpose of the study was to examine the differences in clinical, psychosocial, and demographic factors by sex and weight status.Methods-Baseline data were analyzed from 318 adolescents (mean age = 12.3 ± 1.1 years, 55.0% female, 62.7% white) with type 1 diabetes (T1D) from a multisite clinical trial. Differences were examined between normal weight (body mass index ≥5th and <85th percentile) and overweight/obese (body mass index ≥85th percentile) boys and girls with T1D in clinical, psychosocial, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 60 publications
3
18
0
Order By: Relevance
“…The T1D Exchange recently documented that 36% of adolescents with T1D are overweight/obese [20, 21••], which is consistent with the SEARCH for Diabetes in Youth Study [22] and other US T1D samples [23, 24] but higher than the general population [25]. In addition, Canadian and Polish studies of children and adolescents with T1D found that 35 and 30%, respectively, were overweight/obese [26, 27].…”
Section: Weight Status In Type 1 Diabetessupporting
confidence: 58%
See 1 more Smart Citation
“…The T1D Exchange recently documented that 36% of adolescents with T1D are overweight/obese [20, 21••], which is consistent with the SEARCH for Diabetes in Youth Study [22] and other US T1D samples [23, 24] but higher than the general population [25]. In addition, Canadian and Polish studies of children and adolescents with T1D found that 35 and 30%, respectively, were overweight/obese [26, 27].…”
Section: Weight Status In Type 1 Diabetessupporting
confidence: 58%
“…Many studies have shown that girls and women with T1D are more likely to be overweight and/or obese than are boys and men [21••, 24, 27, 28]. However, Duca and colleagues recently reported that 68 and 59% of men and women were in the overweight/obese weight categories, respectively, with more men classified as obese and more women as overweight [29].…”
Section: Biopsychosocial Factors Related To Weight Statusmentioning
confidence: 99%
“…Moreover, these factors may differentially impact adolescents, as these youth may also encounter issues related to identity, social norms, and gaining independence, which have been found to be related to challenges with diabetes self-management. [2427] Several of these factors have been associated with overweight/obesity among adolescents in the general population, but findings are limited among adolescents with T1D. [4]…”
Section: 1 Introductionmentioning
confidence: 99%
“…Across focus groups, the thematic content and emphasis varied significantly across sex, evidencing the existence of differences in the psychosocial aspects of both weight management (Kaminsky and Dewey, 2014; Minges et al, 2016) and T1DM (Huxley et al, 2015; Powers et al, 2017). The largest sex difference emerged with regard to several weight attitudes and behaviors reported uniquely by females.…”
Section: Discussionmentioning
confidence: 99%